I trust what she's #endorsing on Instagram: moderating effects of parasocial interaction and social presence in fashion influencer marketing. Issue 4 (3rd February 2021) - Jin, S. Venus; Ryu, Ehri; Muqaddam, Aziz
Abstract : Purpose: Social media campaigns by fashion brands typically rely on two types of accounts: official brands' accounts and social media influencers' accounts. The current study investigates relevant mechanisms that explain the effectiveness of Instagram posts contingent upon their account types (commercial brand's Instagram account versus influencer's Instagram account) and content types (the absence versus presence of human figures in the posted contents). Design/methodology/approach: Conducting an online experiment ( N Females = 195), it was tested if parasocial interaction (PSI) and feelings of social presence moderate the effects of Instagram accounts' promotional posts on consumers' perceived trustworthiness of the endorsed fashion brand. The experiment employed a 2 (Type of Instagram posts: product-only posts versus product posts with a person content) × 2 (Type of Instagram account: a fashion-brand account versus a a fashion-influencer account) between-subjects factorial design. Findings: Results demonstrate three-way interaction effects among the type of the Instagram account, the type of Instagram posts and PSI/social presence on the perceived trustworthiness of a brand. When the content is coming from a fashion-influencer account, there is no difference between product posts with a person and product-only posts conditions with regard to the positive relationship between PSI/social presence and trustworthiness. In contrast, when the source is a fashion-brand account on Instagram, the positive relationship between PSI/social presence and trustworthiness is stronger for product posts with a person. These findings suggest that Instagram posts that are promoted by fashion influencers would have similar effects of PSI and social presence, even if they do not appear themselves in the branded content. Originality/value: This research contributes to our understanding of the effective antecedents of trustworthiness in social media-based fashion marketing and fashion brand management. Instagram account types and content types influence the extent to which social media communication allows for the formation of emotional ties with and positive evaluation of the fashion brand.